Nutritional status of adults and children under 5 years of age in two areas of Guatemala Project results for “His and Hers, time and income: how intra-household dynamics impact nutrition in agricultural households”. - Consenza, Emma; Talsma, Elise F.; Arora, Diksha; Twyman, Jennifer; Useche, Pilar; González, Carolina; Lopera, Diana Carolina; Muriel, Juliana (International Center for Tropical Agriculture, 2019)
In this info-note, we explain the body mass index calculations (BMI) for adults in agricultural Guatemalan households, as well as the implementation of indicators to assess the nutritional status of children under 5 years (height for age, weight for age and weight for height). This work is part of the project “His and Hers, time and income: How intra-household dynamics impact nutrition in agricultural households,” led by the International Center for Tropical Agriculture (CIAT) and the University de Florida 1 with funding from the program Innovative Methods and Metrics for Agriculture and Nutrition Actions (IMMANA).2 The prevalence of stunting in Guatemalan children under 5 years is 46 percent, according to Guatemala’s Ministry of Public Health (INE, 2015). Stunting refers to insufficient height with respect to age. It is a consequence of inadequate socioeconomic conditions that are often associated with insufficient nutrition and health of the mother, which is in turn reflected in inadequate care of the infant. Stunting prevents children from fully developing their physical and cognitive potential (WHO, 2018). Simultaneously and paradoxically, Guatemala also shows a significant presence of overweight and obesity rates among its population. The prevalence of overweight in adults is 56% and of obesity is 21% (WHO, 2017).